[Bmmim]6[In10Se16Cl4]·(MIm)2: an organic-ligand free discrete T3 cluster for efficient hydrogen evolution under visible light irradiation. Issue 16 (20th March 2020) - Wang, Yanqi; Hu, Qianqian; Jin, Jiance; Li, Jilong; Li, Jianrong; Huang, Xiaoying
Abstract : An organic-ligand free selenide T3 cluster exhibits a much higher photocatalytic hydrogen evolution activity after being stably dispersed in a solvent (6.5 times) than that in the solid state. Abstract : An indium selenide [Bmmim]6 [In10 Se16 Cl4 ]·(MIm)2 (Bmmim = 1-butyl-2, 3-dimethylimidazolium, MIm = 1-methylimidazole) cluster has been synthesized and characterized. The discrete T3 cluster could be stably dispersed in dimethyl sulfoxide, exhibiting photocatalytic hydrogen evolution activity at least six times that of the pristine in the solid state due to the exposure of more active sites.